2011
DOI: 10.1136/tc.2010.038703
|View full text |Cite
|
Sign up to set email alerts
|

How generalisable to community samples are clinical trial results for treatment of nicotine dependence: a comparison of common eligibility criteria with respondents of a large representative general population survey

Abstract: Further studies and interventions should explore the efficacy of tobacco treatment interventions in a larger segment of the population, notably in the subpopulations of people with nicotine dependence who smoke fewer than 10 cigarettes per day or who have comorbid depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 107 publications
2
54
0
Order By: Relevance
“…77,78 Yet, surprisingly few data exist on the impact of long-term NRT use in terms of health outcomes in the general population. Most data come from clinical trials, which have samples that tend to differ in important ways from general population samples 79 and in which NRT is provided free together with behavioural support, which may affect normal usage patterns. By contrast, most NRT in the UK is used without advice and bought over the counter, 80 and in many other countries (unlike in the UK) it is rarely provided for free on prescription.…”
Section: Rationale and Study Aimsmentioning
confidence: 99%
“…77,78 Yet, surprisingly few data exist on the impact of long-term NRT use in terms of health outcomes in the general population. Most data come from clinical trials, which have samples that tend to differ in important ways from general population samples 79 and in which NRT is provided free together with behavioural support, which may affect normal usage patterns. By contrast, most NRT in the UK is used without advice and bought over the counter, 80 and in many other countries (unlike in the UK) it is rarely provided for free on prescription.…”
Section: Rationale and Study Aimsmentioning
confidence: 99%
“…Clinical trial participants tend to receive more attention and more behavioral support than is typically offered to a primary care patient, and trial participants are often healthier and more motivated than their counterparts in the primary care setting. 6 These differences may contribute to significantly lower medication adherence rates and, as a result, to lower rates of smoking cessation in primary care patients.…”
Section: Variables and Definitionsmentioning
confidence: 99%
“…For example, in the tobacco-dependence fi eld, the median clinical trial has 12 exclusion criteria, and approximately two thirds of smokers in the general population are ineligible under one or more of them (Le Strat et al, 2011). For illicit drug dependence, a review of 98 clinical trials found that less than one third reported information suffi cient to calculate the proportion of screened patients who were eligible and the proportion of the eligible group who agreed to participate (Melberg and Humphreys, 2010).…”
mentioning
confidence: 99%